Chemically modified alginate bead matrix for efficient adsorptive recovery of trypsin from fresh bovine pancreas. (3rd October 2018) - Aravena, Pilar; Brassesco, Maria Emilia; Bosio, Barbara; Picó, Guillermo; Woitovich Valetti, Nadia
Abstract : The adsorption of commercial trypsin (Try) onto epichlorohydrin cross‐linked alginate–guar gum matrix has been studied at equilibrium in batch and in fixed bed column. Experiments were conducted to study the effect of ionic strength, temperature and to obtain a thermodynamic characterization of the adsorption process. The resulting adsorption isotherm fitted the Hill equation. Experimental breakthrough curve profiles were compared with the theoretical breakthrough profiles obtained from the mathematical model, bed depth service time. At pH 5.0, 1.0 g hydrated matrix adsorbed 480.0 milligram of Try per gram of dried bed. The desorption process showed 80% of Try recovery in 50 mM phosphate buffer, pH 7.00—500 mM NaCl—20% propylene glycol. The obtained results were applied to an adsorption/washing/desorption process with fresh pancreas homogenate yielded 20% of recovery and 5.7 purification factor of Try. The matrix remained functional until the fifth cycle of repeated batch enzyme adsorption. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018